Initiation into crime: An analysis of Norwegian register data on five birth cohorts - Taryn Ann Galloway; Stephen Pudney (Statistics Norway, Research Department, 2011)
We construct linked register data on five Norwegian birth cohorts, covering: criminal charges after age 15; family characteristics and history up to age 15; and (for males) IQ test scores. A longitudinal analysis of the risk of initiation into crime in early adulthood suggests an increased risk for the children of young and unmarried mothers and for those experiencing disruptive family events including divorce or maternal death during childhood. There is a relationship between continuity of parental employment and reduced risk, with no evidence of harm from mothers' employment. Cognitive ability remains strongly associated with reduced risk after allowing for family history and circumstances.
Keywords: C33; I18; K42; 330; Norway; Crime; Family; Cognitive ability; Register data